Scaling like behaviour of resistivity observed in LaNiO3 thin films grown on SrTiO3 substrate by pulsed laser deposition - Sergeenkov, S.; Cichetto, L. [UNESP]; Zampieri, M.; Longo, E. [UNESP]; Araujo-Moreira, F. M. (IOP Publishing, 2015)
We discuss the origin of the temperature dependence of resistivity ρ observed in highly oriented LaNiO3 thin films grown on SrTiO3 substrate by a pulsed laser deposition technique. All the experimental data are found to collapse into a single universal curve for the entire temperature interval ( K) with being the onset temperature for triggering a resonant scattering of conduction electrons by spin fluctuations in LaNiO3/SrTiO3 heterostructure.
Keywords: nickelates; resistivity; scaling; spin fluctuations; thin films